2015
DOI: 10.1371/journal.pone.0140371
|View full text |Cite
|
Sign up to set email alerts
|

“Women Are Better Than Men”–Public Beliefs on Gender Differences and Other Aspects in Multitasking

Abstract: Reports in public media suggest the existence of a stereotype that women are better at multitasking than men. The present online survey aimed at supporting this incidental observation by empirical data. For this, 488 participants from various ethnic backgrounds (US, UK, Germany, the Netherlands, Turkey, and others) filled out a self-developed online-questionnaire. Results showed that overall more than 50% of the participants believed in gender differences in multitasking abilities. Of those who believed in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 19 publications
2
24
1
2
Order By: Relevance
“…It is a widely held belief that women outperform men in multitasking situations, possibly because of an evolutionary advantage and extensive multitasking practice resulting from managing children, household, and jobs [1, 2]. In fact, two recent studies showed that the majority of participants was convinced that gender differences in multitasking existed and at least 80% of them attributed better multitasking abilities to women than to men [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…It is a widely held belief that women outperform men in multitasking situations, possibly because of an evolutionary advantage and extensive multitasking practice resulting from managing children, household, and jobs [1, 2]. In fact, two recent studies showed that the majority of participants was convinced that gender differences in multitasking existed and at least 80% of them attributed better multitasking abilities to women than to men [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…The EMS contains some items with a rather liberal interpretation of multitasking, for instance listening to music or singing during an activity. Such activities impose low cognitive demands ( Szameitat et al, 2015 ) and therefore, people are more inclined to engage in them (69% of women and 49% of males, see above). The MPI focusses more on the work context and virtually exclusively uses the terms task and project .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our data are self-rated measures, and that there is little evidence that women actually would engage more in multitasking or that they would be better at it ( Szameitat et al, 2015 ). For instance, Buser and Peter (2011) conducted a study in which participants had to perform several office tasks in different regimes enforcing either single- or multitasking, or leaving the decision to the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations